The multifaceted of themed restaurant: exploring the unique and vulnerable elements in staging authentic dining experience - Che Ishak, Farah Adibah; Zainun, Nur Amira Ashiqin; Karim, M. S.; Ungku Zainal Abidin, Ungku Fatimah; Mohamad, Siti Fatimah (Human Resource Management Academic Research Society, 2020)
The diversity of foodservice establishments in the market not only extending the menu options but also offering a wider range of dining experiences. In particular, dining at a themed restaurant is viewed as an authentic, fun and pleasurable experience. However, a small glitch from the management may turn down the whole dining experience. Thus, the objective of this research is twofold; to identify the uniqueness of the themed restaurant in delivering the authentic dining experience, and to explore the weaknesses leading to the poor dining experience. Through qualitative research, this study has interviewed a number of customers who experienced dining in various themed restaurants across Klang Valley area. Semi-structured interviews had been carried out in the process to assist the researcher in getting a deeper understanding of experience consumption. Participant observation was also executed through field visits to the selected restaurants to get the first-hand experience. Based on the results, it showed that customers enjoyed the dining moments because of the aesthetic facility, comforting ambiance, and attentive service staff. In contrast, including inadequate restaurant maintenance, the contradiction of expectation with reality in food presentation and pricy menu items contribute to poor dining experience. The contributing factors to these experiences were discovered hence filled the gap of previous studies and offer the future researchers a deeper understanding of the themed restaurant’s forte. Practically, the findings can help the existing and new restaurateurs to improve their offerings in staging a unique dining experience that satisfies the customers’ needs and wants.